SIMULAÇÃO DO COMPORTAMENTO TÉRMICO DE ESTUFAS AGRÍCOLAS COM COBERTURA PLÁSTICA - Ferreira, Jorge Luiz (Revista Liberato, 2013)
This work is a resume of the dissertation of same tittle [Ferreira (2002)]. The aim is to model the thermal behavior of an agricultural greenhouse, with an aproximative area of 1500 m2 and with low density polyethylene plastic covering. The equations adopted in this modelling give more importance to the description of the radiant phenomena, that are treated in a more detailed way, if compared to the phenomena of heat transfer by convection and conduction. The model is able to simulate the greenhouse’s internal ambient air temperature, from outside data, like the temperature of the air and the incident solar radiation. The results obtained by the simulation are compared to experimental data, collected along a research project developed in greenhouses for roses production, in the mountain region of Rio Grande do Sul State - Brazil. A good approach level is verified by the simulation when comparing to measured values. Finally, it’s concluded that the model follows the real phenomena, although it requires improvements and consistences.